THE EFFECT OF PROMOTION, PRICE, BRAND IMAGE AND SERVICE QUALITY ON MAXIM'S CUSTOMER SATISFACTION IN PEKANBARU CITY - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 4 No 4 (2024): LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to analyze the effect of promotion, price, brand image and service quality on Maxim's customer satisfaction in the people of Pekanbaru City. Determination of the sample in this study using the Accidental Sampling Method, the number of samples in this study were 110 respondents. In this study, primary data were obtained directly from respondents by distributing questionnaires to the specified sample. The data analysis technique in this study is the Multiple Linear Regression Test with the SPSS application. The results of this study indicate that promotions and prices have no significant effect on Maxim's customer satisfaction in Pekanbaru City. Meanwhile, brand image and service quality have a significant positive effect on Maxim's customer satisfaction in Pekanbaru City.